2011
DOI: 10.1371/journal.ppat.1002189
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Aedes aegypti Transcriptome during Infection with West Nile, Dengue and Yellow Fever Viruses

Abstract: West Nile (WNV), dengue (DENV) and yellow fever (YFV) viruses are (re)emerging, mosquito-borne flaviviruses that cause human disease and mortality worldwide. Alterations in mosquito gene expression common and unique to individual flaviviral infections are poorly understood. Here, we present a microarray analysis of the Aedes aegypti transcriptome over time during infection with DENV, WNV or YFV. We identified 203 mosquito genes that were ≥5-fold differentially up-regulated (DUR) and 202 genes that were ≥10-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
273
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 177 publications
(297 citation statements)
references
References 38 publications
15
273
3
Order By: Relevance
“…The arthropod immune system consists of the RNAi pathway, as well as the Toll, Imd, and Jak-STAT signaling pathways, which result in changes in the transcriptome leading to the production of proviral and antiviral factors. Previously published microarray studies have reported many genes that are regulated in response to alpha-and flavivirus infections in Drosophila S2 cells, Aedes aegypti midguts, and whole Aedes aegypti mosquitoes (25,42,43). In the present study we identified 95 genes with significantly altered expression as a result of SINV replication in whole Drosophila.…”
Section: Discussionmentioning
confidence: 58%
“…The arthropod immune system consists of the RNAi pathway, as well as the Toll, Imd, and Jak-STAT signaling pathways, which result in changes in the transcriptome leading to the production of proviral and antiviral factors. Previously published microarray studies have reported many genes that are regulated in response to alpha-and flavivirus infections in Drosophila S2 cells, Aedes aegypti midguts, and whole Aedes aegypti mosquitoes (25,42,43). In the present study we identified 95 genes with significantly altered expression as a result of SINV replication in whole Drosophila.…”
Section: Discussionmentioning
confidence: 58%
“…Evidence for a transcriptomic signature of flavivirus infection was found during a comprehensive study of Aedes aegypti infected with WNV, DENV, and YFV (42). Genes involved in transcription and ion binding were found to be downregulated, and genes coding for proteases and cuticle proteins were found to be upregulated, during infection with all three viruses (42).…”
Section: Vector Response To Infectionmentioning
confidence: 99%
“…Recent advances in high throughput technologies, such as transcriptomics and proteomics, for pathogen-host interaction studies [25,52,96,109,117,136], as well as the publication of several vector species genomes including the mosquitoes Culex quinquefasciatus [2], Anopheles gambiae [49] and Aedes aegypti [89] and the tick Ixodes scapularis [46], have led to the discovery of immunity pathway orthologues in these species [65,105]. While there is no midge genome available to date, recent combined efforts of The Pirbright Institute and the European Bioinformatics Institute (part of the European Molecular Biology Laboratory; EBI-EMBL) have led to the first full de novo sequencing project for Culicoides sonorensis.…”
Section: Introductionmentioning
confidence: 99%